Chloroquine sensitizes biofilms of Candida albicans to antifungal azoles - Shinde,Ravikumar Bapurao (2013)
Biofilms formed by Candida albicans, a human pathogen, are known to be resistant to different antifungal agents. Novel strategies to combat the biofilm associated Candida infections like multiple drug therapy are being explored. In this study, potential of chloroquine to be a partner drug in combination with four antifungal agents, namely fluconazole, voriconazole, amphotericin B, and caspofungin, was explored against biofilms of C. albicans. Activity of various concentrations of chloroquine in combination with a particular antifungal drug was analyzed in a checkerboard format. Growth of biofilm in presence of drugs was analyzed by XTT-assay, in terms of relative metabolic activity compared to that of drug free control. Results obtained by XTT-metabolic assay were confirmed by scanning electron microscopy. The interactions between chloroquine and four antifungal drugs were determined by calculating fractional inhibitory concentration indices. Azole resistance in biofilms was reverted significantly (p < 0.05) in presence of 250 µg/mL of chloroquine, which resulted in inhibition of biofilms at very low concentrations of antifungal drugs. No significant alteration in the sensitivity of biofilms to caspofungin and amphotericin B was evident in combination with chloroquine. This study for the first time indicates that chloroquine potentiates anti-biofilm activity of fluconazole and voriconazole.